The reasons for nonimplementation of innovative activity at the enterprises of the Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Today competitiveness of the country can be defined by features oftechnological structure in the economy. For example, in our country III TU64%, IV TU – 35%, V TU – 1%. The efficiency of technological modesdue to the development of innovation in the world. Small and mediumbusiness is the main driving force for innovation. Because of this, everycountry is facing problems of development of innovation. Therefore, thereasons for low innovation activity at the enterprises are lack of Finance,small full of lack of demand or an innovative product, the lack of informationabout the market of an innovative product, a shortage of qualified specialistin the field of innovation. In addressing these nuances, the Republicis able to develop small and medium entrepreneurship which is a driver ofthe economy.
Keywords: Small and medium businesses; innovation; innovative entrepreneurship; innovative product.